The Influence of The Student Teams Achievement Division (STAD) Learning Model on The Learning Outcomes of Class V Students Subhtema 1: How The Body Processes Food State Elementary School No. 125138 Pematang Siantar - Irena Nopi Prenti Raja Gukguk; Minar T. Lumbantobing; Hetdy Sitio (International Journal of Integrated Science and Technology, 2023)
The background to this research is based on the observations of Class V researchers at SD Negeri 125138 Pematang Siantar that teachers still use conventional learning models so that students are less involved in the learning process. This causes the learning process to be less than optimal and student learning outcomes do not meet the minimum criteria for perfection. The solution to this problem needs to be found, among others, by implementing the Student Teams Achievement Division learning model . This learning model can be applied to Indonesian and natural science subjects because it encourages students to work together and communicate with each other in completing their assignments. This learning model can improve the quality of Indonesian and science learning so that students are more active, creative, and learning is more meaningful so that learning outcomes improve. This research used a pre-experimental method with a single group pretest-posttest design with a sample size of 38 students. Based on the results of the data analysis tests carried out, the results of the hypothesis testing were tcount = 18.576 and ttable = 2.026 with tcount > ttable = 18.576 > 2.026, so H0 was rejected and Ha was accepted. With this explanation, it can be concluded that there is an influence of the Student Teams Achievement Division learning model on the Indonesian language and science learning outcomes of class V students at SD Negeri 125138 Pematang Siantar.